Discovery of vascular targeting agents from herbal medicines - Cai, Jesmine Xiulian (2011)
Endothelial cells are essential in the regulation of several physiological and pathological processes. Diseases with excessive endothelial cell proliferation, such as cancer, can be treated with vascular targeting agents, which induce endothelial cell death or inhibit endothelial cell proliferation. Given the urgency to seek treatment for these diseases, a high throughput assay for screening vascular targeting agents is important. Recently, an endothelial cell line (HUVEC-C3) from a sensitive FRET-based biosensor that can detect caspase-3 activation in living cells during cell apoptosis has been generated. Using HUVEC-C3, vascular targeting agents can be detected at an accelerated rate. In this study, the capability of several herbal compounds to induce apoptosis has been evaluated using fluorescence assays based on HUVEC-C3. In addition, MTT assays and cell morphological observations were conducted to validate the data. Lower concentrations were conducted to find the optimum dosage of the compounds. This highly efficient screening process has facilitated the identification of vascular targeting agents which can be further developed to treat angiogenesis-associated diseases.